Charakterystyka kliniczna i długoterminowe wyniki pacjentów z glikogenozą typu 1b: retrospektywne doświadczenie wieloośrodkowe w Polsce - Kaczor, Magdalena; Wesół-Kucharska, Dorota; Greczan, Milena; Kierus, Karolina; Kałużny, Łukasz; Duś-Żuchowska, Monika; Ehmke vel Emczyńska-Seliga, Ewa; Ciara, Elżbieta; Książyk, Janusz; Rokicki, Dariusz (Pediatric Endocrinology Diabetes and Metabolism, 2022)
Glycogen storage disease type 1b (GSD 1b) is an inherited metabolic defect caused by a deficiency of microsomal glucose-6-phosphate (G6P) transport protein across the endoplasmic reticulum membrane. Patients with GSD 1b have hypoglycemia episodes, lactate acidosis, hypertriglyceridemia, hypercholesterolemia, hyperuricemia, neutropenia and in imaging studies hepatomegaly and/or nephromegaly. The primary goals of treatment are to maintain proper blood glucose levels and to increase the number of properly functioning neutrophils. The aim of the study was a retrospective analysis of the clinical picture and treatment results of pediatric patients with type 1b glycogen storage disease from Poland. The study included 13 patients from 3 clinical centers, with a median age at diagnosis as 5 months. In 11/13 patients, the diagnosis was confirmed by molecular test, by the presence of pathogenic variants on both alleles of the SLC37A4 gene. Ten out of 13 patients developed the first symptoms in the form of severe infection (sepsis and/or pneumonia) already in the neonatal-infant period. A hypoglycemia episode was observed before diagnosis in 8/13 patients, of which 4/8 patients presented symptoms in the form of generalized relaxation and/or seizures. Two patients developed hypertension, and 4/13 required long-term treatment of inflammatory bowel disease.